2012
DOI: 10.1007/s00210-012-0753-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of simvastatin on isolated rabbit atrioventricular node during experimental atrial fibrillation model: role in rate control of ventricular beats

Abstract: The purpose of the present study was to determine (1) whether simvastatin (SV) modifies the rate-dependent conduction time and refractoriness of the atrioventricular (AV) node and (2) how it can change the protective mechanism of the AV node during atrial fibrillation (AF). Predefined stimulation protocols were applied to detect the electrophysiological parameters of the AV node, including atrial-His conduction time, effective refractory period (ERP), functional refractory period (FRP), concealed conduction, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…A concealed conduction and zone of concealment (ZOC) were calculated as previously defined by Khori et al (2012b). The rate-dependent effects of the ZOC were measured by applying various stimulation cycle lengths (300-160 ms).…”
Section: Stimulation Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A concealed conduction and zone of concealment (ZOC) were calculated as previously defined by Khori et al (2012b). The rate-dependent effects of the ZOC were measured by applying various stimulation cycle lengths (300-160 ms).…”
Section: Stimulation Protocolsmentioning
confidence: 99%
“…ZOC was calculated as the difference between atrial refractoriness (AERP) and nodal refractoriness (NERP). In addition, differences between AH and ERP were measured as the excitability index, indicating the drug's relative effect on nodal conduction time prolongation against refractoriness (Khori et al 2012b(Khori et al , 2015. The AV nodal gap (conduction gap) refers to the duality of the AV node and is defined as a window of each coupling interval, within which the atrial stimulus was not conducted through the AV node.…”
Section: Stimulation Protocolsmentioning
confidence: 99%
“…Direct electrophysiologic effects of statins, including inhibition of ionic currents and expression and synthesis of channel protein, have been established on ventricular and atrial tissue . Our previous study showed that simvastatin (SV) has inhibitory effects on AV node during experimental atrial fibrillation (AF) . Using of the functional model to predict the protective effects of SV during simulate experimental AVNRT would be of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the papers coming from Islamic countries typically have not focused on natural products, but rather on chemically defined substances. Moreover, they represent a broad range of topics such as ischemia/reperfusion injury (Hosseinzadeh et al 2012; M. M. El-Mas : H. M. El-Gowelli Mahmoud et al 2012), atrial fibrillation (Khori et al 2012), allergic airway disease (Nader et al 2012), skeletal muscle (Hosseinzadeh et al 2012;Renno et al 2012), urinary bladder smooth muscle (Balkanci et al 2012), or the metabolism of xenobiotics (Pang et al 2012).…”
mentioning
confidence: 99%